Content analysis of the revised K-13 science textbook grade VII SMP/MTs on disaster risk reduction instruction - Reno Nurdiyanto; Ulil Khasanah; Faizal Kristanto; Pujianto Pujianto (Journal of Science Education Research, 2019)
Textbooks are one of the learning resources that are widely used by students and teachers. Analyzing the contents of a textbooks is a way that can be done to assess the quality of the book. This research aims to determine the content of the revised K-13 science textbook grade VII SMP/MTs which is appropriate for integrated disaster risk reduction learning in schools. The emphasized disaster is a disaster that often occur in Indonesian. This research used document analysis method. Data were collected based on a systematic review of documents and supporting evidence in the form of research on disaster risk reduction in science learning in SMP / MTs. Data were analyzed by using descriptive analysis based on research focus. This research was conducted by analyzing two books from the government and non-government. The result of research shows that there are 19.05% sub material in the science books from the government and 17.2% of non-government that integrated disaster risk reduction. From the result, it can be seen that the content in grade VII SMP / MTs science textbooks on disaster risk reduction is still lack, so it is necessary to add content related to disaster mitigation to the science book grade VII SMP / MTs.